Influence of irrigation methods on arsenic speciation in rice grain. (1st November 2022) - Spanu, Antonino; Langasco, Ilaria; Barracu, Francesco; Deroma, Mario Antonello; López-Sánchez, José Fermín; Mara, Andrea; Meloni, Paola; Pilo, Maria Itria; Estrugo, Àngels Sahuquillo; Spano, Nadia; Sanna, Gavino
Abstract: Although the bioaccumulation of arsenic (As) in rice grains is a global health issue, its speciation is not less worrying. Despite the ascertained effectiveness of the intermittent irrigation methods in minimizing the amount of total As in rice, knowledge of its influence on the As speciation has been insufficient so far. Hence, this contribution was aimed to measure the concentrations of As(III), As(V), dimethylarsinic acid (DMA), and monomethylarsonic acid (MMA) in grains from twenty-six different rice genotypes irrigated either with continuous flooding (CF), periodic saturation (SA) or sprinkler irrigation (SP). In CF-irrigated rice, As(III) and DMA prevailed in roughly equal amounts, only As(III) was found in SA-irrigated rice, whereas As(V) was largely predominant on As(III) in SP-irrigated rice. Organoarsenic species were below the limits of detection (LoD) in rice irrigated by intermittent methods. Principal component analysis (PCA) explained the influence of the irrigation method on the total amount of As, its chemical species, and their correlation. Furthermore, PCA showed also significant differences in As speciation as a function of the rice genotype, whereas no differences were found among Indica and Japonica subspecies. Graphical abstract: Image 1 Highlights: Intermittent irrigations greatly affect the position of As speciation in rice grain. As(III) and DMA are the main As species in rice irrigated by continuous flooding. Only As(III) is present in grains of rice irrigated by periodical saturation. As(V) is predominant rice irrigated by sprinkler, while As(III) is minority in it. Genotypes affects less than irrigations the position of As speciation in kernels.